2011
DOI: 10.1093/sleep/34.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Changes of the Circadian Clock of Humans: Increasing Duration is More Effective than Increasing Light Intensity

Abstract: Results from the present study suggest that for phototherapy of circadian rhythm sleep disorders in humans, a longer period of moderate intensity light may be more effective than a shorter exposure period of high intensity light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 28 publications
6
72
0
1
Order By: Relevance
“…The “dose” of a light exposure is known from basic research studies of humans to be determined by multiple factors (Dewan, Benloucif et al, 2011; Eastman, 2011; Lucas, Peirson et al, 2014). Wavelength is one such factor, but our data suggest that short wavelengths are not crucial for SAD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The “dose” of a light exposure is known from basic research studies of humans to be determined by multiple factors (Dewan, Benloucif et al, 2011; Eastman, 2011; Lucas, Peirson et al, 2014). Wavelength is one such factor, but our data suggest that short wavelengths are not crucial for SAD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies compared different durations of continuous bright light exposures, and showed that longer durations produced larger phase shifts [49, 80, 86]. Previously in our lab, we compared daily bright light (~5000 lux) with durations of 3 or 6 hours along with an abrupt 12-hour shift of sleep/dark for 8 days [49].…”
Section: Discussionmentioning
confidence: 99%
“…The phase shift averaged over the last 4 days was 8.1 hours for the 3-hour duration and 9.4 hours for the 6-hour duration. A second study [86] tested three bright light durations (1, 2, and 3 hours) with different light intensities (2000, 4000, and 8000 lux). Subjects were awakened for a single bright light exposure in the middle of their sleep period before the temperature minimum to produce phase delays.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The intensity, duration of exposure, and wavelength of light also influence the degree to which the circadian clock will phase shift. [11][12][13][14][15][16] The response for melatonin is opposite to light, with melatonin before the T min resulting in a phase advance and melatonin after the T min resulting in a phase delay. 17,18 The largest phase advances are achieved with low doses (3 mg) of melatonin about 4 hours before habitual dim light melatonin onset, or 6 hours before habitual sleep onset.…”
Section: Introductionmentioning
confidence: 99%